PENERAPAN SUPERVISI KLINIS UNTUK MENINGKATKAN MUTU PROSES PEMBELAJARAN SDN 05 KOTO BESAR KECAMATAN KOTO BESAR DHARMASRAYA - Suherman (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2022)
This research originated from SDN 05 Koto Besar, Koto Besar District, that teachers need help planning and implementing the learning process in the classroom. The implementation of the learning process carried out by teachers of SDN 05 Koto Besar, Koto Besar District, Dharmasraya Regency, has yet to be following the Process Standards. The implementation of clinical supervision by the principal is primarily to meet administrative demands, especially in the face of school accreditation, and its implementation has not been referred to the Minister of National Education. Researchers conducted School Action Research (PTS) on SDN 05 Koto Besar, Koto Besar District teachers with a type of classroom visit technique action in clinical supervision to improve the teacher's ability to carry out the learning process. Through two cycles in August and September 2022, the most critical actions are carried out with planning, implementation, observation, and reflection stages. The results of these observations are discussed in the reflection stage to determine the follow-up in cycle II. The implementation of cycle II is based on the results of the reflection of cycle I. It is understood as material for preparing RPP and implementing the learning process that will be carried out in cycle II. The implementation of cycle II was carried out one month later. The reflection of cycle II is used as material for the inference of the results of this PTS. Thus, this pts concluded that the Class Visit Technique in clinical supervision is very effective in improving teachers' ability to implement the learning process. The improvement can be seen in the teachers of grades I to VI with excellent value to improve the quality of the learning process. Therefore, teachers, principals, and supervisors must increase their understanding of the Process Standards and implement them in the learning process (for teachers) and clinical supervision (for principals).